Child's Book of Art great pictures : first words - Micklethwait, Lucy (London ; New York : Dorling Kindersley, 1993)
An introduction to art that uses well-known works of art to illustrate familiar words.
Includes index.
71458
Keywords: Art appreciation -- Juvenile literature; Art appreciation; Vocabulary